Effect of CaO and CeO2 co-doping on thermo-physical properties of La2Z2O7. Issue 4 (1st October 2020) - Luo, Lirong; Xu, Chunhui; Chang, Xiaohong; He, Fujian; Tian, Xiaocong; Lu, Luhua; Chen, Ying; Hou, Shuen; Jin, Hongyun
ABSTRACT: Ce 4+ and Ca 2+ modified La2 Zr2 O7 samples, La2 Zr2 O7, (La0.8 Ce0.2 )2 (Zr0.7 Ce0.3 )2 O7.2 and (La0.6 Ce0.2 Ca0.2 )2 (Zr0.7 Ce0.3 )2 O7, were prepared by the co-precipitation method to obtain enhanced thermos-physical properties. Compared with La2 Zr2 O7, (La0.8 Ce0.2 )2 (Zr0.7 Ce0.3 )2 O7.2 and (La0.6 Ce0.2 Ca0.2 )2 (Zr0.7 Ce0.3 )2 O7 both exhibited better sintering resistance, lower thermal conductivities, and higher thermal expansion coefficients. The underlying mechanism of the improved thermo-physical performance of La2 Zr2 O7 induced by Ce 4+ and Ca 2+ doping was discussed. The thermal conductivity and thermal expansion coefficient of (La0.6 Ce0.2 Ca0.2 )2 (Zr0.7 Ce0.3 )2 O7 were 1.165 W·m −1 ·K −1 at 1450°C and 10.91 × 10 −6 K −1, respectively, making it a promising material for the thermal barrier coatings (TBCs).